The Rules of origin under the CARIFORUM-EU Economic Partnership Agreement (EPA) - Odle, Stanley (CCS GeorgetownGY, 2012)
Explains the rules of origin under the CARIFORUM-EU Economic Partnership Agreement (EPA).